Analisis Perbaikan Kualitas Proses Produksi di PT XYZ Menggunakan Metode Fuzzy FMEA - Made Ayu Chyntia Dewi Puspitaloka; Yurida Ekawati (Teknik Industri Universitas Ma Chung, 2022)
This study focuses on the application of quality control through the FMEA method with the fuzzy approach in the bread food industry. The case study is in PT XYZ, which produces several bread products. The FMEA method is used to identify the potential failure of the production process, but it has a weakness in producing an identical RPN value. To overcome this weakness, the fuzzy approach using the Fuzzy Inference System (FIS) with the Mamdani concept is applied to produce the Fuzzy RPN (FRPN) value. The FRPN calculations can determine the priority improvement in bread products, which can be ranked 1-5. The implementation of the proposed improvements, such as the training of operators, maintenance of machines, repairs of uneven roads, and rest periods for machines, can reduce product disability to 1%. The study shows that the application of the FMEA method with the fuzzy approach is effective in identifying and prioritizing the improvement of product quality in the food industry. The results can help companies to enhance their production process and product quality.